HUBUNGAN PENGETAHUAN DAN FAKTOR MOTIVASI PESERTA PROLANIS DENGAN PARTISIPASI DALAM PROGRAM PENGELOLAAN PENYAKIT KRONIS DI PUSKESMAS KILOMETER 11 KABUPATEN DAIRI TAHUN 2020 - Siregar, Vanni Prayuti (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The efforts made by the government in dealing with chronic diseases in Indonesia through the Chronic Disease Management Program (Prolanis) is a program with a proactive approach that is carried out in an integrated manner by involving the involvement of the Prolanis participants. The purpose of this study was to determine the relationship of motivational factors and knowledge of Prolanis participants in the KM 11 Dairi District Health Center using a cross sectional research design. Total population of 276 people, with a total sample of 73 participants prolanis. The research instrument is the questionnaire. Data analysis methods are univariate, bivariate with chi square test and multivariate with logistic regression test. The results showed that of 73 respondents as many as 43 people (58.9%) had good categories of knowledge. Motivation factors based on the needs of the majority with a low category of 37 people (50.7%), and motivational factors based on the interests of the majority with a low category of 40 people (54.8%). The results of the bivariate analysis addressing knowledge and motivational factors based on interests and expectations have a relationship with the value of p <0.05. The results of multivariate analysis showed that motivational factors based on expectations were the most related factors to participant participation with coefficient values ​​(9,954). It is recommended that the KM 11 Dairi District Health Center be able to increase the promotion efforts and carry out Prolanis activities in a sustainable manner so that Prolanis participant participation can be better.